2015
DOI: 10.25011/cim.v38i3.22703
|View full text |Cite
|
Sign up to set email alerts
|

Serum and urinary biomarkers for predicting acute kidney injury after partial nephrectomy

Abstract: Serum and urinary biomarkers for predicting acute kidney injury after partial nephrectomy Abstract Purpose: The purpose of this study was to evaluate the ability of specific biomarkers to predict acute kidney injury (AKI) after partial nephrectomy.Methods: A prospective study of 89 patients undergoing partial nephrectomy was conducted in the First Affiliated Hospital of Fujian Medical University. The patients were divided into two groups according to AKI status: an AKI group and non-AKI group. Receiver operato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…Secondly, the improvement of surgeons' skill and surgical technique helped preserve renal function. For example, the durations of renal hilus clamping and surgery were shorter in our patients than in previous studies [8,24,25].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Secondly, the improvement of surgeons' skill and surgical technique helped preserve renal function. For example, the durations of renal hilus clamping and surgery were shorter in our patients than in previous studies [8,24,25].…”
Section: Discussioncontrasting
confidence: 68%
“…Routine circulatory management during partial nephrectomy is to maintain blood pressure change within 20% from baseline and urine output > 0.5 ml/kg/h. However, the incidence of AKI remains high after surgery [8,24,25]. Experience from kidney transplantation suggested that maintaining adequate renal hydration and higher blood pressure after reperfusion (i.e., CVP > 8 mmHg and MAP > 95 mmHg) are bene cial for graft function [14,15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty studies161718192021222324252627282930313233343536373839404142434445 finally met the inclusion criteria via full-text evaluation from 156 potentially eligible citations. Seven studies21222324252627 were selected from the previous meta-analysis (Zhang, et al .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies21222324252627 were selected from the previous meta-analysis (Zhang, et al . 2011)15 and an additional 23 studies1617181920282930313233343536373839404142434445 were complemented in the present meta-analysis. A flow chart of the identification and selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unilateral nepherectomy was done according to Chen et al [23]. Rats were anesthetized with sodium pentobarbital (50 mg/kg body weight; ip).…”
Section: Unilateral Nepherectomymentioning
confidence: 99%